Socio-Economic Impact of Mobile Phones on Indian Agriculture - Surabhi Mittal; Sanjay Gandhi; Gaurav Tripathi (Indian Council for Research on International Economic Relations (ICRIER), 2010)
Deficits in physical infrastructure, problems with availability of agricultural inputs and poor access to agriculture-related information are the major constraints on the growth of agricultural productivity in India. The more rapid growth of mobile telephony as compared to fixed line telephony and the recent introduction of mobileenabled information services provide a means to overcome existing information asymmetry. It also helps, at least partially, to bridge the gap between the availability and delivery of agricultural inputs and agriculture infrastructure. This paper investigates a series of questions that explore this topic: What kind of information do farmers value the most to improve agricultural productivity? Do mobile phones and mobile-enabled agricultural services have an impact on agriculture? What are the factors that impede the realisation of the full productivity enhancing potential of mobile phones? The answers to these questions have important implications for mobile operators, for information service providers, and for policymakers. The quality of information, its timeliness and trustworthiness are the three important features that have to be ensured to enable farmers to use it effectively to improve productivity. The study found evidence that mobiles are being used in ways which contribute to productivity enhancement. However, to leverage the full potential of information dissemination enabled by mobile telephony will require significant improvements in supporting infrastructure and capacity building amongst farmers to enable them to use the information they access effectively. As mobile penetration continues to increase among farming communities and information services continue to adapt and proliferate, the scope exists for a much greater rural productivity impact in the future.
Keywords: Q16; Q18; 330; Mobile phones; farmers and fishermen; agricultural productivity; Mobilkommunikation; Agrarproduktion; Landwirtschaftliche Entwicklung; Indien